2022
DOI: 10.21037/tcr-22-310
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy related DNA methylation signature predict clinical prognosis and immune microenvironment in low-grade glioma

Abstract: Background: Low-grade glioma (LGG) is a common malignant tumor of the central nervous system.The clinical prognosis of different patients varies greatly, so exploring appropriate markers that affect the prognosis and treatment of LGG is important. The purpose of this study was to identify the potential effect of autophagy-related DNA methylation on the prognosis and immune microenvironment in LGG. Methods:The methylation profile, transcription data and corresponding clinical information of 451 patients with LG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The significant increase of glycolysis metabolism increases the growth rate, invasion and metastasis ability of LGG cells, and promotes the progress of LGG disease (21). Research shows that the factors causing tumor occurrence, such as the deletion of tumor suppressor gene and the activation of proto oncogene, can cause metabolic changes of tumor cells, and lead to aerobic glycolysis disorder, which can lead to tumor progression (22). As low-grade gliomas are mainly characterized by their IDH mutations, IDH1 and IDH2 are NADP+-dependent enzymes that catalyze the oxidative decarboxylation of isocitrate in the citric acid cycle to α-Ketoglutarate (α-KG).…”
Section: Introductionmentioning
confidence: 99%
“…The significant increase of glycolysis metabolism increases the growth rate, invasion and metastasis ability of LGG cells, and promotes the progress of LGG disease (21). Research shows that the factors causing tumor occurrence, such as the deletion of tumor suppressor gene and the activation of proto oncogene, can cause metabolic changes of tumor cells, and lead to aerobic glycolysis disorder, which can lead to tumor progression (22). As low-grade gliomas are mainly characterized by their IDH mutations, IDH1 and IDH2 are NADP+-dependent enzymes that catalyze the oxidative decarboxylation of isocitrate in the citric acid cycle to α-Ketoglutarate (α-KG).…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that biomarkers including S100A, TEAD4, SRSF9, METTL7B, CSPP1, and CKS2 have significant relevance to the diagnosis and prognosis of LGG patients ( 9 14 ). In addition, iron metabolism-related genes, cuproptosis-related genes, necroptosis-related gene, autophagy-related signatures, as well as autophagy related DNA methylation signature, are also important prognostic factors for LGG ( 15 19 ). However, these clinical pathologic and genetic factors used for predicting LGG in clinical practice is poor, which limits their early diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%